Kebijakan Fiskal dan Pengelolaan Utang Publik: Tantangan dan Peluang di Era Globalisasi - M. Iqbal Febriansyah; Adrian Kurnia Sobana Putra; Muh. Tsaqif Rafii; W Pangestoeti (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study investigates the challenges and opportunities associated with fiscal policy and public debt management in Indonesia during the globalization era, with a particular focus on the 2021–2025 period. Employing a qualitative descriptive approach and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, the research aims to evaluate the effectiveness and resilience of Indonesia’s fiscal strategies amid rapidly shifting global economic conditions. The findings highlight several internal strengths, including the maintenance of macroeconomic stability, prudent fiscal discipline, and efforts to diversify financing sources. However, the study also uncovers significant weaknesses, such as Indonesia’s persistently low tax ratio, inefficient state spending, and the limited capacity of sub-national governments to manage fiscal responsibilities effectively. Externally, globalization presents both opportunities and threats. Opportunities include access to global financial markets, the potential for green financing (e.g., green bonds and SDG bonds), and digital transformation in fiscal governance. On the other hand, threats such as global market volatility, rising interest rates, currency risks, and geopolitical tensions pose serious challenges to fiscal sustainability. The study emphasizes the need for adaptive and forward-looking fiscal policies that can respond to external shocks while maintaining national development priorities. Key policy recommendations include accelerating tax reform, implementing risk-based public debt governance, enhancing synergy between central and regional governments, and strengthening institutional capacity. These measures are crucial to ensure long-term fiscal resilience and support Indonesia’s aspiration to achieve its Golden Indonesia 2045 vision — a future characterized by inclusive growth, economic competitiveness, and sustainable development.